Social environment, emotions, and impulse buying: A mediational analysis - Aouinti, Najla (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Previous research has shown relationships between variables of the retailing environment, such as design and ambiance, and impulse buying. However, little is known about the influence of social environment on this type of purchase. Therefore, the main purpose of this current study is to examine the effect of social environment variables on emotions felt in the point of sale and on achieving an impulse buying. Following a survey conducted in a hypermarket, the results show direct and indirect effects of social environment on making an impulse purchase decision. The pleasure mediates the influence of sales staff on impulse buying. Otherwise arousal has a mediating role in the variables of social environment - pleasure link. Hence, this study provides practical guidance for how retailing firms can manage social environment and emotions felt on the point of sale to induce a rewarding impulse buying experience.